The Effects of CHEETS Nursing Practice on Gross Motor Development of Children with Down Syndrome Aged 11 - 5 Years - Tuchsinpong, Janphen; Soondara, Laddawan; Karittanarut, Pimchanok; Laivanit, Busara (Journal of Health Science of Thailand, 2017)
Gross motor development of children with Down syndrome has severely been delayed because of their hypotonia,ligamentous laxity and decreased strength conditions. The data about gross motor’s Developmental Skills Inventory Index (DSI Index) of children with Down syndrome at Rajanukul Institute was lower than the expected DSI Index target (32.7%). This point has impacted on the effectives and satisfactions of customers. This study was a one group pre test - post test design. The purposes were to examine the effects of CHEETS nursing practice on gross motor skills of children with Down syndrome aged - 5 years, and knowledge of caregivers. The purposive sample consisted of 16 caregivers and 16 children with Down syndrome aged - 5 years. Data were collected from March to May 2011. The processes of the quasi - experiment were divided into four steps. Step I: The knowledge of caregivers and gross motor development of children with Down syndrome were examined. Step II: Individual planning. Step III: Giving knowledge for caregivers about taking care of their children for 3 hours. Gross motor development program was individually provided for the children with Down syndrome for 30 minutes a day for four days in a row. Data collection: Research instruments, consisted of 10 items of knowledge questionnaire and 28 items of gross motor development assessment form, were content validated and tested for reliability coefficient. Caregivers’ knowledge was post tested and children’s gross motor development was evaluated by developmental check list. Data were analyzed by descriptive statistics and paired t-test (p<0.05). The differences of the mean scores of pre-post gross motor development of children with Down syndrome aged - 5 years and caregiver’s knowledge were statistically significant at 0.05 level. CHEETS nursing practice could, therefore, promote gross motor development of children with Down syndrome since this program was designed to help the children individually and enhance knowledge of the caregivers to appropriately take care of their children.